PENGEMBANGAN BUDAYA MUTU DALAM MENINGKATKAN KUALITAS MADRASAH DI MADRASAH IBTIDAIYYAH NEGERI KOTA BANDAR LAMPUNG - Anwar, Syaiful (Analisis: Jurnal Studi Keislaman, 2014)
DEVELOPING A QUALITY CULTURE IN IMPROVING QUALITY OF MADRASAH (Studies in MIN as Bandar Lampung): Quality is important  in human life, both individually, comunally, or socially. Quality can be guaranteed by ensuring that each individual has a capacity needed to carry out the job properly. With the right tools, workers will be able to make products and services in a manner consistent  with the costumer expectations. Quality improvement is a continuous process and without ending. At the institutional level, the development of quality requires the seriousness of all school board members and administrators along with  a mass training  which allows each individual  in school to be trained. This study  explores the quality culture improvement patterns  which are applied in the State  Madrasah Ibtidaiyyah of Bandar  Lampung.  Through  a qualitative   descriptive  approach, this research is expected to give a contribution  in improving the quality of Islamic education in general.